Association between lung function and dyspnoea and its variation in the multinational Burden of Obstructive Lung Disease (BOLD) study - Müller, A. (2024)
Background: Dyspnoea is a common symptom of respiratory disease. However, data on its prevalence in general populations and its association with lung function are limited and are mainly from high-income countries. The aims of this study were to estimate the prevalence of dyspnoea across several world regions, and to investigate the association of dyspnoea with lung function. Methods: Dyspnoea was assessed, and lung function measured in 25,806 adult participants of the multinational Burden of Obstructive Lung Disease study. Dyspnoea was defined as ≥2 on the modified Medical Research Council (mMRC) dyspnoea scale. The prevalence of dyspnoea was estimated for each of the study sites and compared across countries and world regions. Multivariable logistic regression was used to assess the association of dyspnoea with lung function in each site. Results were then pooled using random-effects meta-analysis. Results: The prevalence of dyspnoea varied widely across sites without a clear geographical pattern. The mean prevalence of dyspnoea was 13.7 % (SD=8.2 %), ranging from 0 % in Mysore (India) to 28.8 % in Nampicuan-Talugtug (Philippines). Dyspnoea was strongly associated with both spirometry restriction (FVC<LLN: OR 2.07, 95 %CI 1.75–2.45) and spirometry airflow obstruction (FEV1/FVC<LLN: OR 3.76, 95 %CI 1.04–4.65). These associations did not significantly differ between sexes, age groups or smoking history. The association of dyspnoea with airflow obstruction was weaker among obese participants (OR 2.20, 95 %CI 1.61–3.01). Conclusion: The prevalence of dyspnoea varies substantially across the world and is strongly associated with lung function impairment. Using the mMRC scale in epidemiological research should be discussed.